Strong long-range electron–phonon interaction as possible driving force for charge ordering in cuprates. (1st April 2019) - Myasnikova, A E; Nazdracheva, T F; Lutsenko, A V; Dmitriev, A V; Dzhantemirov, A H; Zhileeva, E A; Moseykin, D V
Abstract: A model resulting in charge ordering (CO) similar to that observed in cuprate superconductors is under study. It includes strong long-range electron–phonon interaction (EPI) and high density of correlated carriers. Coexistence of large bipolarons and delocalized carriers is a feature of such system. We develop generalized variation method to calculate the bipolaron size (CO period) in the ground normal state of such system at various doping. The approach allows the revealing of a possible physical reason of strongly different doping behavior of the CO wave vector in different cuprates. Obtained doping dependences of the CO period and temperature of the CO decay demonstrate quantitative agreement with those observed in cuprates. Predicted in the suggested approach ratio of the CO wave vector to the wave vector of the high-energy anomaly (HEA) in ARPES spectrum is in consent with that in cuprates. Calculated resonant x-rays scattering on the CO emerging in the model is in good agreement with experiments on cuprates including the asymmetry of the CO peaks' cross-section. A gap arises in the spectrum of delocalized carriers near antinodal direction due to their scattering on the periodic potential created by autolocalized carriers, analogously to photon crystal effect.